Size Matters: Why We Love to Hate Big Food - Arnot, Charlie (Springer International Publishing, 2018)
Despite food being safer, more affordable and more available than at any time in human history, consumers are increasingly skeptical and critical of today's food system. In Size Matters, Charlie Arnot provides thought provoking insight into how the food system lost consumer trust, what can be done to restore it, and the remarkable changes taking place on farms and in food companies, supermarkets and restaurants every day as technology and consumer demand drive radical change. The very systems and technologies that are mistrusted by consumers are driving a revolution that empowers individual consumers to find the perfect recipe of taste and nutrition to meet their specific needs and desires. Size Matters pulls back the curtain to examine the irony, competing priorities and new realities that shape today's food system.